Molecular detection and phylogenetic analysis of Peste des petits ruminants virus circulating in small ruminants in eastern Amhara region, Ethiopia - Alemu, Biruk G.; Gari, Getachew; Libeau, Genevieve; Kwiatek, Olivier; Kidane, Menbere; Belayneh, Rediet; Siraw, Bewuket; Wieland, Barbara; Asfaw, Wondwoson; Abdi, Reta D. (Springer, 2019)
Peste des Petits Ruminants (PPR) is a severe, highly infectious and fatal viral disease of small ruminants. Four lineages of PPR virus have been identified globally based on sequence analysis of the nucleoprotein (N) and fusion (F) gene. The aim of this study was to isolate and genetically characterize recently circulating PPR virus in small ruminants in the eastern Amhara region in Ethiopia. A total of 28 anti-mortem samples (gum debris, nasal and ocular swab) were collected from clinically suspicious animals and examined for the presence of PPRV by a one-step RT-PCR assay. Samples positive with RT-PCR were subjected to isolation of the virus which were subsequently genetically characterized by sequencing of the nucleoprotein (N) gene and phylogenetic analysis of PPR virus (PPRV) strains.Of the 28 clinical samples examined, 46.4% were positive with RT-PCR for viral nucleic acid. The PPRV was successfully isolated on CHS-20 cell line with the ovine signaling lymphocyte activation molecule (SLAM) receptor expressed on the cell surface and confirmed with RT-PCR and IFAT assay. The nucleotide sequence and phylogenetic analysis indicated that the PPRV obtained were clustered genetically with Lineage IV isolates of the virus.The successful isolation of the virus and molecular findings of this study confirmed active lineage IV PPRV infections among populations of sheep and goats in eastern Amhara, suggesting risks for potential spread of the disease to currently free areas. Thus, we recommend systematic vaccination to contain outbreaks in affected districts and geographically linked surrounding districts to which the disease could potentially spread due to different epidemiological linkages.